Diseño y construcción de un proyecto de fresadora CNC para piezas de madera para el A.E.I.R.N.N.R. - Estrella González, Geovanny Rigoberto (2012)
In the present project was developed and built a computer numerical control milling machine CNC for machining pieces of wood, which will serve to develop prototypes of machine elements. We performed the conceptual design of the machine, manufacturing technology and the operating manual and in compliance with all regulations of industrial safety. Finally, we conducted performance tests results taking as a versatile machine built with materials that are available in the industry and a number of standardized components that make it a viable solution for machining by chip removal, cutting, shaping and polishing wooden elements, ensuring precision and quality.